A Focused Library of NO‐Donor Compounds with Potent Antiproliferative Activity Based on Green Multicomponent Reactions. (23rd August 2019) - Ingold, Mariana; Colella, Lucía; Hernández, Paola; Batthyány, Carlos; Tejedor, David; Puerta, Adrián; García‐Tellado, Fernando; Padrón, José M.; Porcal, Williams; López, Gloria. V.
Abstract: Cancer is the second leading cause of death worldwide. Herein, a strategy to quickly and efficiently identify novel lead compounds to develop anticancer agents, using green multicomponent reactions followed by antiproliferative activity and structure–activity relationship studies, is described. A second‐generation focused library of nitric oxide‐releasing compounds was prepared by microwave‐assisted Passerini and Ugi reactions. Nearly all compounds displayed potent antiproliferative activities against a panel of human solid tumor cell lines, with 1‐phenyl‐1‐[( tert ‐butylamino)carbonyl]methyl 3‐[(3‐phenylsulfonyl‐[1, 2, 5]oxadiazol‐4‐yl N 2 ‐oxide)oxy]benzoate (4 k ) and N ‐[1‐( tert ‐butylaminocarbonyl)‐1‐phenylmethyl]‐ N ‐(4‐methylphenyl)‐3‐(3‐phenylsulfonyl‐[1, 2, 5]oxadiazol‐4‐yl N 2 ‐oxide)oxyphenyl carboxamide (6 d ) exhibiting the strongest activity on SW1573 lung cell line (GI50 =110 and 21 nm ) with selectivity indices of 70 and 470, respectively. Preliminary mechanistic studies suggest a relationship between NO release and antiproliferative activity. Our strategy allowed the rapid identification of at least two molecules as future candidates for the development of potent antitumor drugs. Abstract : The eco‐friendly synthesis via multicomponent reactions and biological evaluation of a series of novel NO donors is presented. All compounds were examined for their activity against six different solid tumor cell lines as well as against non‐tumorigenic mammalian cells to investigate their selectivity. To examine the relationship between NO release and antiproliferative activity, the cytotoxic activity was evaluated in the presence of a well‐known NO scavenger. Compounds4 k and6 d arise as candidates for further studies.